(untitled) (Journal of Forensic Medicine & Toxicology, 2012)
Electricity becomes the integral part of the modern world. By human it can be used both in productive and destructive way. By using the same electricity in a different condition we save the life of the patients in the emergency wards and intensive care unit [ICU] in the form of cardio version with the paddle called defibrillator. Here we present a case of a male child who got electrocuted accidentally while playing cricket, by the high voltage overhead line thus he lost his vision of both the eyes, because of herniation of the brain through the entry wound.